Global boundedness in a two-species predator–prey chemotaxis model. (January 2021) - Miao, Liangying; Yang, He; Fu, Shengmao
Abstract: This paper is devoted to investigate the global boundedness of a two-species predator–prey chemotaxis model with one signal. By establishing the uniform boundedness of L 2 -norm for prey and predator densities and the uniform boundedness of L 4 -norm for the signal gradient, we consider the global existence and boundedness of classical solutions to the model in a three-dimensional bounded domain.